Redox properties of flavocytochrome c3 from Shewanella frigidimarina NCIMB400. - Turner, K; Doherty, M; Heering, H; Armstrong, F; Reid, G; Chapman, S (1999)
The thermodynamic and catalytic properties of flavocytochrome c3 from Shewanella frigidimarina have been studied using a combination of protein film voltammetry and solution methods. As measured by solution kinetics, maximum catalytic efficiencies for fumarate reduction (kcat/Km = 2.1 x 10(7) M-1 s-1 at pH 7.2) and succinate oxidation (kcat/Km = 933 M-1 s-1 at pH 8.5) confirm that flavocytochrome c3 is a unidirectional fumarate reductase. Very similar catalytic properties are observed for the enzyme adsorbed to monolayer coverage at a pyrolytic graphite "edge" electrode, thus confirming the validity of the electrochemical method for providing complementary information. In the absence of fumarate, the adsorbed enzyme displays a complex envelope of reversible redox signals which can be deconvoluted to yield the contributions from each active site. Importantly, the envelope is dominated by the two-electron signal due to FAD [E degrees ' = -152 mV vs the standard hydrogen electrode (SHE) at pH 7.0 and 24 degrees C] which enables quantitative examination of this center, the visible spectrum of which is otherwise masked by the intense absorption bands due to the hemes. The FAD behaves as a cooperative two-electron center with a pH-dependent reduction potential that is modulated (pKox at 6.5) by ionization of a nearby residue. In conjunction with the kinetic pKa values determined for the forward and reverse reactions (7.4 and 8.6, respectively), a mechanism for fumarate reduction, incorporating His365 and an anionic form of reduced FAD, is proposed. The reduction potentials of the four heme groups, estimated by analysis of the underlying envelope, are -102, -146, -196, and -238 mV versus the SHE at pH 7.0 and 24 degrees C and are comparable to those determined by redox potentiometry.